Structural Locality and Early Stage of Aggregation of Micelles in Water: An Adaptive Resolution Molecular Dynamics Study. Issue 6 (2nd May 2018) - Shadrack Jabes, B.; Klein, Rupert; Delle Site, Luigi
Abstract: The adaptive resolution simulation technique is employed to perform molecular dynamics simulations of a single micelle and two micelles in water. It is shown how, by identifying the essential atomistic degrees of freedom in the solvation process, the adaptive technique can be used to devise an optimal strategy for studying the aggregation of two micelles with atomistic accuracy and at a reduced computational cost. Atomistic accuracy is highly desired in such studies; in fact, if any water‐mediated effect that requires the explicit hydrogen bond network is present, then the adaptive resolution will be able to describe it. Instead, this is not possible if a generic coarse‐grained model, for example, spherical molecules without orientational bonds, is employed. In particular, the potential of mean force for the aggregation of two micelles is calculated and it is shown that the results obtained agree in a satisfactory way with the full atomistic simulation of reference. In perspective, this paper offers an example of how similar systems/problems can be efficiently treated with the adaptive resolution technique. Abstract : Using the adaptive resolution simulation technique an optimal strategy is employed to study the aggregation of amphiphilic aggregates in solution.